TANTANGAN DAN STRATEGI DALAM PELAKSANAAN SAFARI TASMI’ DI PPTQ MBS DAARUN NAJAH DI MASYARAKAT - Azka Rahmawati; Siti Choiriyah (Pascasarjana Universitas Al-Qolam Malang, 2026)
This study explores the challenges and strategies in implementing the Safari Tasmi’ program at the Tahfidzul Qur’an Muhammadiyah Boarding School (PPTQ MBS) Daarun Najah Klaten. Safari Tasmi’ is one of the pesantren’s hallmark programs designed not only to evaluate students’ Qur’an memorization but also to serve as a form of da’wah and social engagement between the pesantren and the surrounding community. Using a qualitative descriptive phenomenological approach, this research investigates both internal and external obstacles faced in the program’s execution and the adaptive strategies employed to overcome them. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The results reveal that the main internal challenges include students’ self-confidence, memorization consistency, and program sustainability, while external challenges involve limited public enthusiasm, communication barriers, and time constraints. The pesantren’s strategies include strengthening hafalan mentoring, character building, public communication management, and community involvement. The study concludes that Safari Tasmi’ functions not only as a memorization event but also as a social-religious movement that integrates spiritual education with community empowerment.